SELF EFFICACY DAN KECEMASAN DALAM MENGHADAPI TUGAS AKHIR PADA MAHASISWA UKWMS - Sarah Florencea; Elisabet Widyaning Hapsari (Universitas Katolik Widya Mandala Surabaya, 2019)
This study aims to determine the relationship of anxiety to students who take the final assignment as a requirement for graduating undergraduate students at UKWMS in terms of self efficacy. Based on one of the factors that can affect anxiety, namely low self efficacy. The link between anxiety facing the final task with self efficacy is that if students believe that they do not have the ability to overcome stressful challenges in the face of the final task, the student will feel increasingly anxious when faced with these challenges. When students have high self-efficacy, the student can overcome the anxiety he faces and challenging or difficult conditions can be likened to a challenge that need not be avoided. The subjects in this study were 341 UKWMS students who were facing the final assignment. The sampling technique used is proportional stratified random sampling. The results of statistical processing obtained a correlation coefficient of -0.376 with a p value of 0.000 (p